Characteristics of Brown Seaweeds Sargassum policystum and Padina minor from Pohuwato Water, Gorontalo - Shindy Hamidah Manteu; Nurjanah Nurjanah; Tati Nurhayati (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2018)
Brown seaweed is one of the abundant resources that grows on the reefs of Pohuwato, Gorontalo Province. This research was aimed to determine the characteristics of S. polycystum and P. minor as sources of salt for hypertensive patients. The research consisted of proximate analysis, minerals, heavy metals, extraction, phytochemicals, phenols analysis, and antioxidant activity. S. polycystum, P. minor had water content of 17.69-22.31%, ash 24.51-30.53%, fat 0.50-0.52%, protein 3.65-4.78%, carbohydrates 53.66-41.88 and crude fiber 3.81-6.52%. The seaweeds also contained Mg 8.89-22.41 mg/g, Fe 0.50-1.00 mg/g, K 26.90-32.71%, Na 22.23-22.69 mg/g, Ca 18.06-32.91 mg/g and ratio Na:K 0.69-0.83 mg/g. Heavy metals were detected in low levels with the content<0.002-<0.004 ppm. Ethanol extract of S. polycystum contained flavonoid, saponin, streoid, alkaloid. Meanwhile ethanol extract of P. minor contained flavonoid, saponin, triterpenoid, stereoid, phenol, dan alkaloid. Total phenol level of S. polycystum was 173.6 mg GAE/g and P. minor was 568.7 mg GAE/g. The antioxidant IC50 of S. Polycystum was 77.58 mg/L while P. minor was 66.38 mg/L.